Discriminant Models as a Tool for Assessing Corporate Bankruptcy Risk - Mariusz CHUDZICKI; Bartłomiej PŁOSZAJ (Communications of International Proceedings, 2025)
Many discriminant models have been developed to assess corporate bankruptcy risk, and they are widely regarded as effective tools for the early identification of financial distress. This study aimed to evaluate the impact that the Covid-19 pandemic and the war in Ukraine had on PSB Mrówka sp. z o.o., a Polish company operating in the retail sector. The analysis employed multiple discriminant models, including both Polish and foreign ones. The findings demonstrated that none of the models classified the company as being at risk of bankruptcy during the examined period. Nonetheless, a marked decline in the values of several discriminant functions was observed, particularly in 2022 and 2023, indicating a deterioration in the company’s financial condition. Models specifically calibrated for Polish enterprises most consistently reflected this downward trend, while selected foreign models suggested a modest improvement in 2023. Overall, the results indicated that although PSB Mrówka maintained a low level of bankruptcy risk, its financial resilience weakened over time. The study concluded that adverse macroeconomic conditions—including elevated inflation, higher interest rates, and geopolitical instability—exerted a negative influence on the company’s financial standing and contributed to a gradual increase in its bankruptcy risk.
Keywords: discriminant models; bankruptcy; financial ratios; forecast